1986
DOI: 10.1007/bf00508426
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 3H-dopamine in megakaryocytes and blood platelets measured by quantitative electron-microscope autoradiography

Abstract: We studied the uptake of dopamine by mature megakaryocytes and blood platelets in mouse spleen after a single intraperitoneal injection of 3H-dopamine. In order to compare the uptake of 3H-dopamine in mature megakaryocytes and blood platelets, we used quantitative autoradiography at the electron-microscope level. Dense accumulations of silver grains were observed on both mature megakaryocytes and blood platelets; all other tissue elements of the spleen exhibited considerably less dense labeling. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In fact, the delayed appearance of thrombocytopenia after [1311]MIBG therapy and its progressive severity in patients previously treated with radio-01-chemotherapy, suggests an earlier cause, most likely by damage to the progenitor mcgakaryocytes. It has been demonstrated that megakaryocytcs are as potent as platelets in concentrating various monoamines (Schick and Weinstein, 1981;Daimon and David, 1986), and contain a radiosensitive nucleus (Tanum, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the delayed appearance of thrombocytopenia after [1311]MIBG therapy and its progressive severity in patients previously treated with radio-01-chemotherapy, suggests an earlier cause, most likely by damage to the progenitor mcgakaryocytes. It has been demonstrated that megakaryocytcs are as potent as platelets in concentrating various monoamines (Schick and Weinstein, 1981;Daimon and David, 1986), and contain a radiosensitive nucleus (Tanum, 1984).…”
Section: Discussionmentioning
confidence: 99%